ENCOURAGING CRITICAL THINKING: "BUT . .. WHAT DOES THAT MEAN?" - Hemming, Heather E. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2000)
ABSTRACT. Encouraging critical thinking requires refinement and growth in the process. While educators often agree that critical thinking is valuable and should be a part of the curriculum there is a pervasive vagueness about what this means. In order that critical thinking be understood, that it be regarded as more than a cliché or slogan, sorne clarification is necessary. This article explores the nature of critical thinking through a discussion on the use of logic, the role of the critical spirit, dialogical reasoning, assessment of criteria, the relationship of content, and the relationship of caring and connections with criticism. RÉSUMÉ. Si les éducateurs s’entendent souvent pour dire que la pensée critique est une chose valable qui devrait être intégrée aux programmes d’études, elle n’en reste pas moins une notion vaguement définie. Certaines précisions s’imposent donc si l’on veut que cette notion soit bien comprise et ne soit plus considérée comme un simple cliché ou slogan. Cet article traite de la nature de la pensée critique par le biais d’une analyse portant sur l’usage de la logique, le rôle de l’esprit critique, le raisonnement dialogique, l’évaluation des critères, la pertinence du contenu et de l’attachement et les liens avec la critique.